PENENTUAN LAJU PEMBENTUKAN GULA REDUKSI ECENG GONDOK PADA PROSES HIDROLISIS KOMBINASI DENGAN BAKTERI SELULOLITIK - Rizka Novembrianto; Muslikha Nourma Rhomadhoni (Envirotek : Jurnal Ilmiah Teknik Lingkungan, 2021)
The presence of water hyacinth in massive numbers will be a problem for surface water. However, water hyacinth also contains cellulose which can be converted into reducing sugar as an ingredient for making bioethanol. This study aims to determine the yield of reducing sugar in the combined hydrolysis stage with cellulolytic bacteria and its maximum reaction rate. Water hyacinth needs that are used are the substrate at a variation of 0.025; 0.057; 0.100; 0.161 and 0.232% (w / v). Pretreatment segment used Phanerochaete chrysosporium mold and continued chemical hydrolysis with treatment of 0.25% and 2% H2SO4 and hot variations of 100 + 3 oC and the combination using Cellvibrio for 24, 48, 72, 96 and 120 hours. The research was carried out at room temperature. The method for measuring reducing sugar using Nelson-Somogyi. Reduction sugar that has been produced in the pretreatment process is a variety of P. chrysosporium fungi, hydrolysis of 0.25% H2SO4 and heating (boiling) 100 + 3oC for 30 minutes and Cellvibrio with the highest yields on water hyacinth substrate 20 g and time 96 hours. The maximum reducing sugar formation rate (Vmax) was 0.762 mg/g/hour and Km was 0.03%.